2011
DOI: 10.1083/jcb1943oia7
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin deficiency is associated with reduced neutrophil recruitment but increased vascular permeability in vivo

Abstract: The maintenance of vascular barrier integrity is crucial during many pathophysiological processes and requires coordinated molecular events including signaling and cytoskeletal remodeling. Cortactin is an actin‐binding protein that regulates actin dynamics and related signaling events. To analyze the role of cortactin in vascular barrier functions, we generated cortactin‐deficient mice. Classical Miles assays revealed that vascular permeability is increased in these mice. Despite this leakiness, leukocyte extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 63 publications
4
45
1
Order By: Relevance
“…Our results with N-WASP depletion are important and striking because loss of function phenotypes for many actin regulatory proteins, including regulators of Arp2/3 complex, feature defects in endothelial monolayer integrity (8,13,24). However, biochemical and cell biological studies reveal that different Arp2/3 regulators, present at the same time and location in the cell, have different functions (25,26).…”
Section: Discussionmentioning
confidence: 95%
“…Our results with N-WASP depletion are important and striking because loss of function phenotypes for many actin regulatory proteins, including regulators of Arp2/3 complex, feature defects in endothelial monolayer integrity (8,13,24). However, biochemical and cell biological studies reveal that different Arp2/3 regulators, present at the same time and location in the cell, have different functions (25,26).…”
Section: Discussionmentioning
confidence: 95%
“…Activated endothelium forms ring-like membrane structures enriched with ICAM-1 and VCAM-1 that are maintained for the duration of transmigration (55). Recent studies have found evidence that neutrophil integrin engagement of ICAM-1 may trigger the disassembly of the VE-cadherin and consecutive encapsulation of the transmigrating leukocyte in "domes," as mice lacking cortactin, a cytoskeletal molecule serving as an adaptor protein to ICAM-1, failed to initiate transmigration (56). For a detailed review of the endothelial molecules involved in this step, see Williams et al (54).…”
Section: Leukocyte Recruitmentmentioning
confidence: 99%
“…The transendothelial migration of isolated human neutrophils through a monolayer of cultured HUVECs was performed, as described previously (24). Briefly, 6.5-mm Transwell filters (Corning Life Sciences, Corning, NY) were coated with fibronectin (0.01%) for 1 h. HUVECs were seeded into the wells and grown to confluence for 2 d. HUVECs were stimulated with TNF-a (5 nM; PeproTech) for 16 h. Human neutrophils were isolated from whole blood by Histopaque density centrifugation, resuspended in control plasma or plasma obtained from placebo-or lidocaine-treated septic patients at different time points, and incubated at 37˚C for 30 min.…”
Section: In Vitro Transmigration Assaymentioning
confidence: 99%